Cooperative Principle Appliance on Daily Conversation of The Verneuil - Sastrawan, I Gede Agus; ., Sajarwa (Humanis; Vol 26 No 1 (2022)DO - 10.24843/JH.2022.v26.i01.p05, 2022)
Communication is a complex linguistics phenomenon. People use various types of utterances to deliver the intended meaning. This article explains the application of Gricean conversational implicature in the daily exchange of The Verneuil. Besides, this study employs the descriptive-qualitative method. As language usage coheres with context, accordingly, this needs to describe the language phenomenon performed by the interactants along with the speech events in which The Verneuil’s dialogue takes place. Thus, utterances are the type of data analyzed. In particular, the article only scopes the circumcision and family lunch scene where they are conflicting with each other because of their different beliefs. Despite the presence of cultural boundaries, the interactants adhere to Grice’s maxims in casual communication. However, maxims’ infringements happen when they get the cultural inferences involved. Those are triggered by the 5 different cultures which affect their linguistics competencies. Hence, they fail to fulfill the maxim.